Copula-an alternative approach to IBNR reserving - Tan, Wei Qiang (2013)
This project examines the dependence structure between 2 variables – developmental time and claim size using copulas, in order to evaluate the incurred but not reported (IBNR) claim reserves more accurately. It also seeks to present a general framework with clear steps and R codes for researchers or practitioners make reference if they wish to apply the copula method in practice.